Effectiveness of Individual Play therapy on Hope, Adjustment and Pain Response of Children with Leukemia Hospitalized in Shahrivar Hospital, Rasht, Iran - Behdokht Alavi1; Behnam Makvandi; Parviz Asgari; Fardin Moradimanesh (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Childhood cancer is a grueling event that can affect the lives of patients and their parents both psychologically and physically. Playing is a way to reduce this problem in children with cancer. Objectives: The aim of this study was to evaluate the effectiveness of individual play therapy on hope, adjustment and pain response of hospitalized children with cancer. Methods: This quasi-experimental study was performed among 30 children with cancer aged 8 to 12 years. Subjects were randomly divided into experimental and control groups. In the experimental group, individual play therapy intervention was performed for two months (10 sessions). The study instruments included: Snyder's Hope Scale, Pediatric Pain Response Questionnaire (Walker et al.), and Dokhanchi's Adjustment Questionnaire (1998). In order to analyze the data, repeated measures analysis and Bonferroni post hoc test were performed in SPSS, version 16. Results: In this study, the mean age of participants in the experimental and control groups was 9.36±1.68 and 10.1±1.98 years, respectively. The results of this study showed that the difference between the three evaluation stages in all variables, except the post-test with the follow-up of hope variable, was significant in the experimental group (p≥0.001). But no significant difference was observed between the three evaluation stages in the control group (p≤0.001). Conclusion: It seems that play therapy intervention has an effect on the research variables. Given that the research was conducted on a small sample in a hospital, it is suggested that similar research be conducted to increase the external validity of the present study.